The Emerging Role of Extracellular Vesicle Derived From Neurons/Neurogliocytes in Central Nervous System Diseases: Novel Insights Into Ischemic Stroke - Li, Fan; Kang, Xiaokui; Xin, Wenqiang; Li, Xin (Frontiers in Pharmacology, 2022)
Abstract Neurons and neurogliocytes (oligodendrocytes, astrocytes, and microglia) are essential for maintaining homeostasis of the microenvironment in the central nervous system (CNS). These cells have been shown to support cell-cell communication via multiple mechanisms, most recently by the release of extracellular vesicles (EVs). Since EVs carry a variety of cargoes of nucleic acids, lipids, and proteins and mediate intercellular communication, they have been the hotspot of diagnosis and treatment. The mechanisms underlying CNS disorders include angiogenesis, autophagy, apoptosis, cell death, and inflammation, and cell-EVs have been revealed to be involved in these pathological processes. Ischemic stroke is one of the most common causes of death and disability worldwide. It results in serious neurological and physical dysfunction and even leads to heavy economic and social burdens. Although a large number of researchers have reported that EVs derived from these cells play a vital role in regulating multiple pathological mechanisms in ischemic stroke, the specific interactional relationships and mechanisms between specific cell-EVs and stroke treatment have not been clearly described. This review aims to summarize the therapeutic effects and mechanisms of action of specific cell-EVs on ischemia. Additionally, this study emphasizes that these EVs are involved in stroke treatment by inhibiting and activating various signaling pathways such as ncRNAs, TGF-β1and NF-κB.